On the uncertain nature of speech rhythm and its relevance in L2 acquisition - Espinosa, Gonzalo Eduardo (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
This article is aimed at reviewing the different accounts for speech rhythm in the languages of the world. It addresses three main aspects in the literature on rhythm based on an impressionistic description, on a phonological explanation, and on the implementation of metrics to measure speech quantitatively. Some relevant studies on L1 speech rhythm are discussed in order to see the different attempts to categorize languages and to describe linguistic variations. In addition, the comparison of Germanic and Romance rhythm leads to the analysis of non-native speech with implications for the teaching and learning of L2 prosody, specifically in the acquisition of English rhythm by Spanish learners.